Search for sharp and smooth spectral signatures of μν SSM gravitino dark matter with Fermi-LAT - Gomez Vargas, German Arturo (2017)
The μνSSM solves the μ problem of supersymmetric models and reproduces neutrino data, simply using couplings with right-handed neutrinos ν's. Given that these couplings break explicitly R parity, the gravitino is a natural candidate for decaying dark matter in the μνSSM. In this work we carry out a complete analysis of the detection of μνSSM gravitino dark matter through γ-ray observations. In addition to the two-body decay producing a sharp line, we include in the analysis the three-body decays producing a smooth spectral signature. We perform first a deep exploration of the low-energy parameter space of the μνSSM taking into account that neutrino data must be reproduced. Then, we compare the γ-ray fluxes predicted by the model with Fermi-LAT observations. In particular, with the 95% CL upper limits on the total diffuse extragalactic γ-ray background using 50 months of data, together with the upper limits on line emission from an updated analysis using 69.9 months of data. For standard values of bino and wino masses, gravitinos with masses larger than about 4 GeV, or lifetimes smaller than about 1028 s, produce too large fluxes and are excluded as dark matter candidates. However, when limiting scenarios with large and close values of the gaugino masses are considered, the constraints turn out to be less stringent, excluding masses larger than 17 GeV and lifetimes smaller than 4 × 1025 s.